A design of faceted search engine - A review - Mahdi, Mohammed Najah; Ismail, Roslan; Ahmad, Abdul Rahim; Thambiratnam, Kavintheran; Mohammed, Abdulameer Mohammed (Science Publishing Corporation, 2018)
The World Wide Web (WWW) allows the people to share information and data from large database repositories globally. The amount of information is already in the billions of databases. We need to search the information with specialize tools known generically as search engine (SE). With the huge data that needs to be handled, search engines need to retrieve meaningful information intelligently, whereby only information of interest to the searcher needs to be returned. Facets (the particular aspect or feature of something being searched) can play an important role in helping the user understand an information space better. Queries techniques within faceted search will make the search results immediate and the interaction between searcher and search engine uninterrupted and focused. They can contribute to the user's understanding of the researched terms or topics. Furthermore, they are more fun and interesting to use because users directly manipulate the search controls and the results can be displayed through choices of presentation such as text displays, transition animations, graphs etc. which bring the process closer to an experience in game playing. This paper review the design of faceted search engine.